CALCULATION OF INCOME FROM CONSTRUCTION WORK IN CONSTRUCTION ORGANIZATIONS AND THEIR RELATED CLAIMS - I.B.Sapayev; S.I.Pirmanova; Sh.I.Norimanov; H.A.Mustafoyeva; D.D.Doniyorov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Income from construction works is one of the main sources of profit in construction organizations. In accordance of our republic "Income from main economic activity", in order to recognize and reflect the income from construction works in accounting, they must meet the following conditions: firstly, the right of ownership of income by the construction organization is confirmed by relevant documents testifying to the fact that the completed construction works have been handed over to the customers; secondly, the amount of income to be received is clear; thirdly, there is full confidence that the proceeds from the performed works will lead to an increase in the assets of the construction organization or a decrease in its liabilities; fourthly, the customer’s unconditional confirmation of the amount of the obligation to the contractor for the construction work received.